"My Personal Teaching Principle is ‘Safe, Fun, and Clear’": Reflections of a TESOL Teacher - Thomas S. C. Farrell; Jessilyn Kennedy (Iranian Journal of Language Teaching Research, 2020)
Reflection and reflective practice have now become common terms used in teacher education and development programs worldwide. Reflective practice generally means that teachers subject their own beliefs and practices of teaching and learning English to speakers of other languages to a critical examination. The increase in popularity of reflective practice in the field of TESOL has also brought about an array of different definitions and approaches most of which however originate from the general education literature. Thus, Farrell (2015; 2019b) developed a holistic framework for TESOL teachers to reflect, that includes reflections on five different stages, the TESOL teachers’ philosophy, principles, theory, practice, and beyond practice. This paper outlines a case study of the reflections of a TESOL teacher through the lens of this framework for reflecting on practice. Overall, the results revealed that many of Lisa’s reflections in all five stages of the framework appear to be connected through two common themes: Teaching to students’ needs and goals and student engagement and rapport building.